Securities transaction tax-case study of India - Neha Malik (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Security Transaction Tax (STT) was introduced in the Indian capital market in 2004. It is a tax on transaction of equities as well as their derivatives. Despite the reduction in STT over the years, it constitutes a large percentage (next only to brokerage fee) of the total cost of trading. The rationale behind STT was to replace the long-term capital gains tax and create a level playing field for all participants in the stock market. It was also seen as a way to mobilise additional revenue. Against this backdrop, the paper examines the trends in the Indian stock market in the past decade and attempts to quantify the impact of STT imposition and subsequent revisions on volatility and trading volume during Oct 2003-July 2013. Empirical results show a mixed response of volatility and volume to changes in STT. Even though STT has contributed to the exchequer, it can be argued that the absence of such a tax could have added more to economic growth and hence, higher revenues by promoting smooth operation of the capital market.
Keywords: G10; G14; G17; G18; G19; 330; Security Transaction Tax; Equity Market; Equity Derivatives; Volatility; Trading Volume; Liquidity